Effect of fermented milk Pediococcus acidilactici BK01 on cholesterol and microbiota in Wistar mice intestine (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study examines the effect of fermented milk containing the probiotic Pediococcus acidilactici BK01 on cholesterol and intestinal microbiota. Materials and Methods: 24 male rats weighing an average of 200 gm each spent 1 week in a cage adapting to their new environment. They were fed standard feed daily and were allowed to drink ad libitum. For 3 weeks, rats were divided into four groups (doses of fermented milk): M+ (control), M1 (0.35 ml), M2 (0.70 ml), and M3 (1.05 ml). The analysis includes bodyweight determination, serum biochemical analysis, and intestine microbiota analysis. Results: The results indicated that while P. acidilactici BK01 fermented milk did not affect body weight or high-density lipoprotein, it did have a beneficial effect on total serum cholesterol and triglyceride levels. Additionally, treatment of fermented milk with P. acidilactici BK01 has been shown to increase the total lactic acid bacteria (LAB) in the intestine, as indicated by changes in the intestinal villi. Conclusion: Administering fermented milk (P. acidilactici BK01, 1.05 ml) can reduce total serum cholesterol and increase the number of LAB in intestinal villi in experimental animals, so it has the potential to be a probiotic.J. Adv. Vet. Anim. Res., 10(1): 64–71, March 2023http://doi.org/10.5455/javar.2023.j653